6 kW/cm2 UVC laser threshold in optically pumped lasers achieved by controlling point defect formation. (27th July 2018) - Kirste, Ronny; Guo, Qiang; Dycus, J. Houston; Franke, Alexander; Mita, Seiji; Sarkar, Biplab; Reddy, Pramod; LeBeau, James M.; Collazo, Ramon; Sitar, Zlatko
Abstract: Optically pumped lasing from AlGaN/AlN multiple quantum wells grown on single-crystalline AlN substrates with lasing thresholds as low as 6 kW/cm 2 is demonstrated via the reduction of unintentional point defects in the active region and waveguide, which reduces the non-radiative recombination by 2 orders of magnitude. A higher lasing threshold of 11 kW/cm 2 is observed for AlGaN barriers, owing to the reduced localization of electrons and holes in the wells. It is shown that for electrically injected UVC laser diodes, AlGaN barriers are essential.